2019
DOI: 10.1039/c8cc09964b
|View full text |Cite
|
Sign up to set email alerts
|

A tumor-targeting Ru/polysaccharide/protein supramolecular assembly with high photodynamic therapy ability

Abstract: A supramolecular assembly was conveniently constructed and exhibited excellent photodynamic therapy selectivity towards tumor cells and negligible toxicity towards normal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…Liu and coworkers synthesised a poly-phenanthroline Ru II photosensitizer with 3 pendant cyclodextrin groups which strongly associate with adamantane-functionalized transferrin molecules via non-covalent binding of the adamantane group to the cyclodextrin cavity. [18] Notably, the resulting supramolecular assembly exhibited selective accumulation in A549 lung cancer cells through transferrin receptor-mediated endocytosis, displaying promising PDT efficiency. Interestingly, glutathione was found to have a protective role in A549 cells during irradiation treatment with this supramolecular system.…”
Section: Protein-assisted Delivery Of Metal-based Photosensitizersmentioning
confidence: 99%
“…Liu and coworkers synthesised a poly-phenanthroline Ru II photosensitizer with 3 pendant cyclodextrin groups which strongly associate with adamantane-functionalized transferrin molecules via non-covalent binding of the adamantane group to the cyclodextrin cavity. [18] Notably, the resulting supramolecular assembly exhibited selective accumulation in A549 lung cancer cells through transferrin receptor-mediated endocytosis, displaying promising PDT efficiency. Interestingly, glutathione was found to have a protective role in A549 cells during irradiation treatment with this supramolecular system.…”
Section: Protein-assisted Delivery Of Metal-based Photosensitizersmentioning
confidence: 99%
“…Our previous research showed that Ru‐HOP‐CD emits ultrahigh near‐infrared fluorescence with excellent fatigue resistance, making it an ideal photosensitizer. [ 17 ] Here, we found that owing to the presence of the dithienylethene unit, complex 1 could undergo reversible photocyclization. Notably, the emission of Ru‐HOP‐CD overlapped poorly with the absorption of ring‐opened 1 (OF‐ 1 ) but showed good overlap with the absorption of ring‐closed 1 (CF‐ 1 ), implying the possibility of photoswitchable fluorescence resonance energy transfer (FRET) from Ru‐HOP‐CD to CF ‐1 .…”
Section: Methodsmentioning
confidence: 92%
“…Ru‐HOP‐CD was synthesized in satisfactory yield by means of our reported method and was fully characterized. [ 17 ] OF ‐1 was synthesized as shown in Scheme S1, Supporting Information: treatment of 3 with 1‐(adamantan‐1‐yl)‐2‐bromoethanone in acetone containing K 2 CO 3 produced OF‐ 1 (81% yield), which was fully characterized by 1 H and 13 C NMR spectroscopy and high‐resolution mass spectrometry. OF‐ 2 nanoparticles were then synthesized by adding an aqueous solution containing Ru‐HOP‐CD and cetrimonium bromide to a glass vial coated with a thin‐film polymer prepared from OF ‐1 and Pluronic F‐127.…”
Section: Methodsmentioning
confidence: 99%
“…Significantly, the resultant Ru/polysaccharide/protein complex exhibited not only specific targeting properties toward tumor cells but also high PDT ability under visible light irradiation. Furthermore, the assembly showed selective killing toward tumor cells combined with negligible toxicity toward normal cells [19].…”
Section: Macrocycle-based Supermolecules As Antitumor Agentsmentioning
confidence: 99%